Instructors’ reasons for choosing problem features in a calculus-based introductory physics course - Edit Yerushalmi; Elisheva Cohen; Kenneth Heller; Patricia Heller; Charles Henderson (Physical Review Special Topics. Physics Education Research, 2010)
This study investigates how the beliefs and values of physics faculty influence their choice of physics problems for their students in an introductory physics course. The study identifies the goals these instructors have for their students, the problem features they believe facilitate those goals, and how those features correspond to problems they choose to use in their classes. This analysis comes from an artifact-based interview of 30 physics faculty teaching introductory calculus-based physics at a wide variety of institutions. The study concludes that instructors’ goals and the problem features they believe support those goals align with research-based curricular materials intended to develop competent problem solvers. However, many of these instructors do not use the beneficial problem features because they believe these features conflict with a more powerful set of values concerned with clarity of presentation and minimizing student stress, especially on exams.